Palestinian Scientific Research from the Perspective of Master’s Students: Exploring Reality and Aspirations - Matar, Osama; Jawabreh, Reem; Radwan, Haya; Alhajhamad, Abedelrahman; Ayyash, Mohammad; Kaleef, Sherin; Gharabeh, Thaher; Abualrob, Ashraf; Halabi, Aseel; Abu Shomer, Diya (Arab Journal for Sciences and Research Publishing, 2023)
The current study aimed to identify the current situation of Palestinian scientific research between reality and hope from the point of view of master’s students. The sample consisted of 206 male and female researchers, who were selected randomly. The researchers prepared a questionnaire consisting of 21 items as a study tool for data collection. The results showed a set of challenges and obstacles faced by Palestinian researchers, and most of these challenges were the lack of funding for scientific research, the lack of training opportunities for scientific research outside the framework of universities, in addition to the lack of ability and knowledge of scientific research and publishing strategies. The study recommended a set of recommendations, the most important of which is increasing government support and allocating a budget for scientific research in addition to the participation of the private sector, promoting and motivating Palestinian researchers through material and non-financial awards, and strengthening the global presence of Palestinian universities and participation in Arab and Western scientific conferences.